Evolutionary Algorithm Based Extreme Learning Machine for Retrieval of Images - Muralimohanbabu, Y.; Radhika, K.; Naga Jyothi, D. (International Journal of Engineering and Technology, 2018)
In the present days, the importance of digital media or images has been improved. All the fields are utilizing these services at their maximum levels. It is because of easy acquisition, easy transmission, easy saving, easy retrieving, easy error correcting, etc. The cost of the storage devices also has been reasonable. Different storage or data servers are maintained to store these digital images. The storage capacity basically depends on image type, number of pixels of the image, number of grey levels of the image, number of dimensions of the image, number of features available in the images, etc. This paper presents an adaptive methodology for medical image retrieval.Â Â
Keywords: Local Binary Patterns; Rotation; Dominant; Features; Image retrieval.